2020
DOI: 10.1039/d0ob01007c
|View full text |Cite
|
Sign up to set email alerts
|

Nitroalkanes as electrophiles: synthesis of triazole-fused heterocycles with neuroblastoma differentiation activity

Abstract: We discovered a reaction of nitroalkanes with 2-hydrazinylquinolines, 2-hydrazinylpyridines and bis-2,4-dihydrazinylpyrimidines in polyphosphoric acid (PPA) affording 1,2,4-triazolo[4,3-a]quinolines, 1,2,4-triazolo[4,3-a]pyridines and bis[1,2,4]triazolo[4,3-a:4',3'-c]pyrimidines, respectively. The reaction expands the scope of heterocyclic annulations involving...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a]pyridines (16) [37] (Scheme 2). Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a]pyridines (16) [37] (Scheme 2). Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…These entities readily react with amines B to afford amidinium intermediates C , which can be used for the highly efficient assembly of imidazoles or oxazoles ( D ) [ 20 , 21 ], as well as imidazolines [ 22 ] and other nitrogen-based heterocycles [ 23 , 24 ]. Furthermore, the reaction with 2-hydrazinylpyridines H enacts formation of the corresponding (hydrazineyl)alkaniminium species I , which was found to undergo intramolecular cyclocondensations to obtain 1,2,4-triazolo[4,3- a ]pyridines ( J ) ( Scheme 1 ) [ 2 ]. Similarly, a mechanistically related reaction with acylhydrazides E proved useful for cyclization toward 1,3,4-oxadiazoles G .…”
Section: Resultsmentioning
confidence: 99%
“…There is significant emphasis on the role of [1,2,4]triazolo[4,3- a ]quinolines in modern-day drug discovery and medicinal chemistry. This privileged scaffold was utilized in the design of potent and selective aldosterone synthase inhibitors with antihypertensive activity [ 1 ], as well as prospective antitumor [ 2 , 3 ], anticonvulsant [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], anti-inflammatory [ 11 , 12 ], and antimicrobial [ 13 , 14 ] agents. It was also found that an introduction of a heterocyclic substituent at C-5 could allow for the preparation of chimeric scaffolds with improved biological activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also shown that a nucleophilic attack on the phosphorylated nitronate species 2 can be carried out with the participation of N-acylhydrazides or thiosemicarbazides to afford the 1,3,4oxadiazoles 9 [45] and the 1,3,4-thiadiazoles 10 [46], respectively (Scheme 1). Finally, it was found that the reaction of 2-hydrazinylpyridine with electrophilically activated nitroalkanes provides the corresponding triazolopyridines 11 (Scheme 1) [47]. These results prompted the desire to implement this general scheme in order to access highly important imidazo [1,5a]pyridines.…”
Section: Resultsmentioning
confidence: 99%